Drinking in social groups. Does 'groupdrink' provide safety in numbers when deciding about risk?. (June 2014) - Hopthrow, Tim; Randsley de Moura, Georgina; Meleady, Rose; Abrams, Dominic; Swift, Hannah J.
Abstract Aims To investigate the impact of alcohol consumption on risk decisions taken both individually and while part of a four‐ to six‐person ad‐hoc group. Design A 2 (alcohol: consuming versus not consuming alcohol) × 2 (decision: individual, group) mixed‐model design; decision was a repeated measure. The dependent variable was risk preference, measured using choice dilemmas. Setting Opportunity sampling in campus bars and a music event at a campus‐based university in the United Kingdom. Participants A total of 101 individuals were recruited from groups of four to six people who either were or were not consuming alcohol. Measurements Participants privately opted for a level of risk in response to a choice dilemma and then, as a group, responded to a second choice dilemma. The choice dilemmas asked participants the level of accident risk at which they would recommend someone could drive while intoxicated. Findings Five three‐level multi‐level models were specified in the software program HLM 7. Decisions made in groups were less risky than those made individually (B = −0.73, P < 0.001). Individual alcohol consumers opted for higher risk than non‐consumers (B = 1.27, P = 0.025). A significant alcohol × decision interaction (B = −2.79, P = 0.001) showed that individual consumers privately opted for higher risk than non‐consumers, whereas risk judgements made in groups of either consumers or non‐consumers were lower. Decisions made by groups of consumers were less risky than those made by groups of non‐consumers (B = 1.23, P < 0.001). Conclusions Moderate alcohol consumption appears to produce a propensity among individuals towards increased risk‐taking in deciding to drive while intoxicated, which can be mitigated by group monitoring processes within small (four‐ to six‐person) groups.